EKSISTENSI NILAI-NILAI PANCASILA DALAM PEMBAHARUAN HUKUM EKONOMI SYARI’AH DI INDONESIA - Chintya, Aprina (Justitia et Pax, 2017)
Since the emergence of Law No. 3 of 2006 on Religious Courts which states that sharia economy is an absolute authority of religious courts. When such authority becomes the jurisdiction of the religious courts, a complete codification of shari'a economic law is required so that the law has legal certainty and the judges have standard reference in solving cases of dispute in sharia business. Pancasila as a life guidance, norms fundamental staats, ground norm, and life of the Indonesian people requires that every rule under it must be based on the values that exist in Pancasila. Renewal of shari'ah economic law is a political Islam discourse that still must prioritize the existence of Pancasila values in the legislation established. The idea of enacting shari'ah economic law should promote the nationalistic tradition and pluralistic values even in its determination to adopt Islamic law.Keywords: Pancasila, syari'ah economic law, Indonesia, norms fundamental staats.